THE INFLUENCE OF TAURINE SUPPLEMENTATION IN LACTOSE EGG YOLK GLYCEROL EXTENDER FOR CRYOPRESERVATION OF BUFFALO BULL (B UBALUS BUBALIS) SEMEN - D. H. Mughal; A. Ijaz; M. S. Yousaf; H. Rehman; M. Aleem; H. Zaneb; I. Rabbani; F. Wadood (Journal of Animal and Plant Sciences, 2013)
The objective of this study was to assess the influence of supplementing various concentrations of taurine in lactose egg yolk glycerol extender (LEGE) on spermatozoa characteristics. Ejaculates of four routinely used Nili- Ravi buffalo bulls were collected once in a week for five weeks using an artificial vagina at Semen Production Unit, Qadirabad, Sahiwal, Pakistan. Pooled semen samples were diluted at 37°C in LEGE extender containing taurine (TA) (0.0, 20.0, 40.0, 60.0 mM) and aspirated into French straws (0.5 ml) having 20 × 106 spermatozoa. Filled and sealed semen containing straws were cooled from 37 to 4°C in a cold cabinet for 4 h before placing it 4 cm above liquid nitrogen (LN) vapors for 20 minutes and stored in LN. These stored straws were thawed individually at 37°C for 30 s in a water bath for evaluation of spermatozoa characteristics such as motility, viability, acrosomal/plasma membrane/DNA integrity and lipid peroxidation. The results indicate that spermatozoa motility (%) significantly decreased (P0.05) among control (TA 0.0), TA 20.0 and TA 40.0 mM supplemented groups. Similarly, spermatozoa DNA integrity rate (%) was significantly decreased (P<0.05) in TA 40.0 and TA 60.0mM supplemented groups as compared to control group. In conclusion, TA supplementation in LEGE at 20.0, 40.0 and 60.0 mM was unable to produce significant effect on spermatozoa characteristics such as viability, acrosomal integrity, plasma membrane integrity and lipid peroxidation compared to control group
Keywords: Nili Ravi; semen quality; taurine; lactose extender; cryopreservation